Performance Comparison of Islamic and Conventional ETFs: Evidence from U.S. Equity Markets - Halber Palaguna Haana (SHACRAL: Shari'ah Economics Review Journal, 2026)
ABSTRACT This study examines the performance comparison between Islamic and conventional exchange-traded funds (ETFs) in the U.S. equity market using daily data. The sample consists of two Shariah-compliant ETFs (SPUS and HLAL) and two conventional benchmark ETFs (SPY and VTI), covering 1,542 observations. Returns are calculated as logarithmic changes in adjusted closing prices. The analysis evaluates both absolute and risk-adjusted performance through descriptive statistics, Sharpe ratios, mean difference tests, and regression models. The findings indicate that Islamic ETFs exhibit slightly higher Sharpe ratios compared to conventional benchmarks, suggesting competitive risk-adjusted performance. However, Welch mean difference tests reveal no statistically significant differences in average returns between Islamic and conventional ETFs. Regression results further demonstrate strong market integration, with Islamic ETF returns closely tracking conventional market returns. Coefficients near unity and high explanatory power indicate that Shariah-compliant ETFs largely reflect broader market dynamics. Overall, the results suggest that Islamic ETFs neither underperform nor outperform conventional ETFs in a statistically meaningful way. These findings support the view that Shariah-compliant investment vehicles can serve as viable alternatives within developed capital markets without sacrificing performance or increasing risk.